Assessment of Disease-related Knowledge Among Children With Inflammatory Bowel Disease and their Family Using IBD-KID2: Evaluating Tool Generalizability. Issue 3 (12th August 2021) - Vernon-Roberts, Angharad; Lopez, Robert N.; Lewindon, Peter; Lemberg, Daniel A.; Bowcock, Nerissa L.; Alex, George; Otley, Anthony; Jacobson, Kevan; Roberts, Amin J.; Evans, Helen M.; Gearry, Richard B.; Day, Andrew S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Children with inflammatory bowel disease (IBD) and their families benefit from improved knowledge of their disease and treatment. Knowledge levels of individual family members are infrequently studied but may identify where education is best directed. We aimed to assess disease-specific knowledge among children with IBD, parents, and siblings, using a validated assessment tool (IBD-KID2), and to establish generalizability of IBD-KID2. Methods: Children with IBD and family members were recruited from tertiary IBD clinics in New Zealand, Australia, and Canada. All participants completed IBD-KID2 online at baseline, and the children with IBD again after 2 weeks to assess reliability. Results: Participants included 130 children with IBD, 118 mothers, 55 fathers, and 37 siblings. Children with IBD had a mean score of 9.1 (SD 2.9) (maximum 15 points), significantly lower than parents ( P < 0.005) and higher than siblings ( P < 0.005). Scores of children with IBD were positively associated with current age ( P < 0.005), age at diagnosis ( P = 0.04) and fathers education level ( P = 0.02). Significant score correlations were seen between children with IBD and their mother ( P < 0.005) but not father. Sibling scores were not correlated with either parent. Test–retest reliability was high. The cohorts from each country were comparable, and no difference in group scores was seen between countries. Conclusion: IBD-KID2 is a generalizable and reliable tool for the assessment of disease and treatment knowledge for children with IBD and their families. Score correlations between parents and children with IBD suggest transfer of knowledge, but sibling knowledge is low and targeted education may be beneficial.